KEPENTINGAN AMERIKA SERIKAT MENOLAK IMPOR CPO (CRUDE PALM OIL) DARI INDONESIA TAHUN 2012 - Siti Masruroh; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to explain the United States the interests to refuse the import of (Crude Palm Oil) CPO Indonesia in 2012. The United States is a potential market in the vegetable oil trade. This opportunity used by Indonesia to increase the CPO market to the United States. However, Indonesia efforts to increase the import of CPO to the United States are in trouble because the US refuses to import CPO from Indonesia by issuing research results from USEPA / EPA (United State Environmental Protection Agency) namely NODA (Notification Of Data Availability).Data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis. The author used Mercantilism approach from Alexander Hamilton and nation-state level analyse. The theories used in this research consist of International Relations, the national interest by Thomas Oatley and Protectionism by Alexander Hamilton.The results of the EPA report that Indonesia's CPO is not environmentally friendly and exceeds the Greenhouse Gas (GHG) emission reduction limit of 11-17 % which should be at the level of 20%. The United States is conducting research because it is linked to an increase in America's biodiesel program. However, the American study proved to be not real. US refusal efforts are seen as an American effort to protect the domestic vegetable oil market, because America does not want CPO products to control the market share of vegetable oil in the country. And another reason, America which is the main producer of soybean oil does not want CPO products to compete with soybean oil as biodiesel fuel.Keywords : Greenhouse Gas Emission, America’s Biodiesel Program, Notification Of Data Availability, United State Environmental Protection Agency, Protection